INVESTIGATION OF SUBSURFACE STRUCTURES WITHIN PARTS OF NIGER DELTA, NIGERIA, VIA AEROMAGNETIC DATA - Ekpa, Moses M; Ibuot, Johnson Cletus; Okeke, Francisca N.; Obiora, Daniel N. (International Journal of Advances in Applied Sciences, 2021)
Geophysical study involving aeromagnetic method was carried out to investigate partsof Niger Delta in Nigeria, aimed at investigating the cause and nature of anomalous bodies within the study area. Spectral analysis technique was employed in quantitative interpretation to determine depth/thickness of the sedimentary basin, basement topography, structural trends,curie point depth, thermal gradient and heat flow in the area. The total magnetic intensity (TMI) anomalies had values of between -53.7nT and 119.5nT while the residual magnetic intensity ranged from -52.5 to 58.0nT. The spectral analysis revealedthe depth to magnetic sources varying from 2.5 to 5.5km while the shallow magnetic sources varied from 0.89 to 1.47km. The geothermal analysis revealed the curie point depth between 11.782 and 18.048km while the calculated geothermal gradient ranged lie between 32.137 and 49.231o . The heat flow values ranged from 80.343 to 123.080 . The results from this study have thrown more light to the understanding of the variation of subsurface structures in the study area. These will enhance the development of the resources and will be of economic benefit to the country if well harnessed. However, possible future research work on this active area is proposed for more robust results.